Consumer protection in e-commerce: Some notes on the Iraqi Electronic Signature and Transactions Act - Aziz, Zana Ismael; Ayub, Zainal Amin; Mohamed, Khadijah (IJMR, 2016)
Inany electronic contract (e-contract) transactions, confidence is considered as a paramount importance for the parties involved. The legal protection for the consumer all stages of e-contract are crucial particularly to avoid any unfair conditions that may be imposed by the dominant party towards the consumer who usually considered as a weaker party in the contract. Given the nature of e contract,the risk posed to consumer is greater than the risk in the traditional trade because the scope of e-commerce is more comprehensive and broader.The aim of this paper is to examine the extent of confidence provided by the Iraqi law to protect consumer in e-contract transactions under its Electronic Transactions Act.The methodology used in this paper is a pure library research focusing mainly on primary and secondary sources. As comparison, there are claims of the adequate protection for the consumer in the electronic contracts in the European Union included in the European directives such as the requirement of informing the consumer in his language, the right to withdraw from the contract and the right to obtain the information. Hence, this paper attempts to demonstrate that the Iraqi’s Electronic Transactions Act lacks these basic rights,and needs further improvements to offer better protection to the consumers.